Culturing Stool Specimens for Campylobacter spp., Pennsylvania, USA - M’ikanatha, Nkuchia M. (Centers for Disease Control and Prevention, 2012)
In 2010, we surveyed 176 clinical laboratories in Pennsylvania regarding stool specimen testing practices for enteropathogens, including Campylobacter spp. Most (96.3%) routinely test for Campylobacter spp. In 17 (15.7%), a stool antigen test is the sole method for diagnosis. We recommend that laboratory practice guidelines for Campylobacter spp. testing be developed.